ANALYSIS OF THE FACTORS THAT INFLUENCE THE DECISION TO PURCHASE "MINYAK KITA" COOKING OIL: A MEDIATION STUDY OF PURCHASE INTENTION AMONG HOUSEWIVES IN PEKALONGAN - Anggik Septianingrum; Panca Kurniati; Eliya Tuzaka (STABILITY : Journal of Management and Business, 2025)
The demand for cooking oil in Indonesia continues to increase along with its role as a basic necessity. The government launched the “Minyak Kita” program as simple packaged cooking oil at affordable prices. This study aims to analyze the effect of price perception, product quality, brand image, and brand trust on purchasing decisions with purchase intention as a mediating variable. This research is quantitative in nature. The research population is housewives who use Minyak Kita in Pekalongan. The sample was determined using purposive sampling technique as many as 185 respondents. Data collection was carried out through a questionnaire. The results showed that price perception, brand image, and brand trust had a significant effect on purchasing decisions, both directly and through purchase intention. However, product quality has no significant effect. This study underscores the importance of building reasonable price perceptions and strengthening brand image and trust to improve purchasing decisions, especially in household consumers.